The Languages of the Scientific Writing: A Review - I Wy. Dirgayasa (Universitas Negeri Medan, 2019)
Writing scientific writing is not essay and simple. Many writers often fail to communicate the idea or subject matter to the readers. The failure to communicate and deliver the idea is due to two factors- the lack mastery of the idea or subject matter itself and poor mastery of the language usage in scientific writing. In term of scientific writing, the language usages are typical ones and standard. This paper attempt to sum up and paraphrase the typical language of the scientific writing covering a) subject and action, b) cohesion and coherence, and c) concision and simplicity